Equivalent‐circuit–based modeling of the scattering and noise parameters for multi‐finger GaAs pHEMTs. (1st March 2019) - Caddemi, Alina; Cardillo, Emanuele; Crupi, Giovanni
Abstract: This study is focused on the experimental characterization of the high‐frequency linear behavior of interdigitated gallium arsenide (GaAs) pseudomorphic high‐electron‐mobility transistors (pHEMTs) in terms of scattering and noise parameters. A measurement‐based model is developed by using the equivalent‐circuit representation. The values of the extrinsic bias‐independent elements are obtained by means of the "cold" approach and then subtracted from the scattering parameter measurements at the bias point of interest, thereby enabling calculation of the intrinsic bias‐dependent elements. Next, the extracted small‐signal equivalent circuit is expanded by assigning an equivalent noise temperature to each resistor, thus obtaining the noise model. The validity of the extracted equivalent‐based model is fully confirmed by the good agreement between measurements and model simulations over a broad frequency range for devices having different number of gate fingers. In addition, the scaling of the achieved performance versus the total gate width is analyzed and discussed.